The genome sequence of a braconid wasp, Microplitis deprimator (Fabricius, 1798) [version 1; peer review: 2 approved] - Gavin R. Broad; Hannah King (Wellcome Open Research)
We present a genome assembly from an individual female braconid wasp, Microplitis deprimator (Arthropoda; Insecta; Hymenoptera; Braconidae). The genome sequence has a total length of 233.20 megabases. Most of the assembly (99.12%) is scaffolded into 11 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 19.62 kilobases in length.